“TA‘A>RUF” DI KALANGAN REMAJA DALAM TINJAUAN PSIKOLOGI HUKUM ISLAM - Abdul Aziz (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
A style of ta‘a>ruf (make a date) for young people in the modern era has given effects in woories among many people. Because romantic in their understanding is based on romantic which made many risks like touching, hug, kissing, and even intercouse. The real effect for young people is giving a support to make love and making intercouse as source for just making fun. This article is oriented to finding an Islamic concept for making a date problem. Because in one side Islam is allowed muslim to love and to be loved, and other side Islam forbid an action when love acrrosed out of Islamic ethic and it has be done in toucing phisically. In addition, a making date is a step for married and as knowing for a candidate of couples (husban and wife) to know their religion, belief, ethic, psychology and other aspects.